Development and Validation of the Patient Experience Assessment Scale (PXAS) in Tertiary Care Hospital - Oman - Naima Khamis Al-Bulushi MD, FFR RCSI; Zainab Ali Al-Mukhaini MD, DCH, DTM&H, MSc, PhD; Jehan Al Fannah BSc, MSc, MBA; Afaf Ali Al Zadjali BSN, MBA; Huda Al Zidi BSc; Zubaida Mahmood Al-Balushi NNP BSN, MBA; Aida Khalfan Al-Hadidi IBCLC; Samir Al-Adawi BSc, MSc, PhD (Journal of Patient Experience)
Background: Evaluating the patient's perspective is crucial for high-quality healthcare. Traditional satisfaction surveys have limitations due to subjectivity. Valid ecological measures are lacking in non-western populations. Objective: Validate Patient Experience Assessment Scale (PXAS) for tertiary care hospital. Methods: The development of PXAS involved domain identification, scale creation, language review, and validity assessment. Experts crafted a 12-question scale with a net promoter score (NPS). Language experts reviewed for clarity and equivalence. The content and face validity were evaluated using the content validity index (CVI) and the face validity index. SPSS analyzed data for reliability and test-retest over 3 to 4 weeks. Results: 464 participants were included, mainly aged 31 to 40, participated. PXAS showed good reliability (Cronbach's alpha = 0.88) and test-retest (r = 0.72). The content validity (I-CVI: 0.83-1.0; S-CVI = 0.93) and the validity of the face (98.3% agreement) were excellent. Most were satisfied (45% excellent and 41.2% very good), and 37% would highly recommend the hospital. Conclusions: PXAS is reliable and valid scale to assess the patient experience in tertiary hospitals. Further studies of its properties are warranted.